Sexual transmission of Zika virus on Twitter: A depoliticised epidemic. Issue 11 (1st November 2020) - Valente, Pablo K.; Morin, Céline; Roy, Melissa; Mercier, Arnaud; Atlani-Duault, Laetitia
ABSTRACT: During global health crises, different narratives regarding infectious disease epidemics circulate in traditional media (e.g. news agencies, television channels) and social media. Our study investigated the narratives related to sexual transmission of Zika virus that circulated on Twitter during a public health emergency and analyzed the relationship between information on Twitter and on traditional media. We examined 10, 748 tweets posted during the peaks of Twitter activity between January and March 2016. Posts in English, Spanish, French, and Portuguese and websites linked to tweets were manually reviewed and analyzed thematically. During the study period, there were three peaks of Twitter activity related to the sexual transmission of Zika. Most tweets in the first peak ( n = 412) had humorous/sarcastic content (55%). Most tweets in the second and third peaks ( n = 5, 154 and n = 5, 182, respectively) disseminated information (>93%). Across languages, textual and visual content on the websites were predominantly placed online by traditional media and highlighted epidemiological narratives published by public health agencies, with little or no mention of the concerns or experiences of individuals most affected by Zika. Prioritising epidemiological/clinical aspects of epidemics may have a depoliticising effect and contribute to overlooking socio-economic determinants of the Zika epidemic and issues related to reproductive justice.